Aleš Ušeničnik in Izidor Cankar: soočenje njunih literarnoestetskih pogledov ob Domu in svetu l. 1916 - Ogrin, Matija (Slavistična revija, 1998)
The article analyzes the fundamental views of Aleš Ušeničnik and Idzidor Cankar on Slovene literature. First it describes their understanding of culture and art in a broades philosophical and esthetical respect. In view of this the second part of the article presents the confrontation of their ideas in their polemic on Dom in svet in 1916.
Keywords: art; Cankar, Izidor; culture; Dom in svet; filozofija; kultura; philosophy; polemike; Slovene literature; slovenska književnost; umetnost; Ušeničnik, Aleš